2006
DOI: 10.1590/s1679-62252006000300005
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive biology of a population of Gymnotus aff.carapo (Teleostei: Gymnotidae) from southern Brazil

Abstract: The reproductive period and its relation with somatic and abiotic factors, the relative and absolute fecundity, spawning type, length of first maturation and sex ratio is describe for Gymnotus aff. carapo from a small lake at Itapuã State Park, Rio Grande do Sul, Brazil. Gymnotus aff. carapo presents a relatively long reproductive cycle extending from November/2003 to March/ 2004. Decreases in water conductivity and increases in dissolved oxygen are correlated with increased gonadal development in males. In fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 16 publications
3
26
0
6
Order By: Relevance
“…A negative correlation to some environmental variables (DO and pH) was observed only for the abundance of G. carapo, which suggests that this species can tolerate adverse physicochemical conditions. This tolerance was also observed by Cognato and Fialho (2006), who found that females of this species presented an increase in gonadal development correlated to a decrease in dissolved oxygen levels.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…A negative correlation to some environmental variables (DO and pH) was observed only for the abundance of G. carapo, which suggests that this species can tolerate adverse physicochemical conditions. This tolerance was also observed by Cognato and Fialho (2006), who found that females of this species presented an increase in gonadal development correlated to a decrease in dissolved oxygen levels.…”
Section: Discussionsupporting
confidence: 78%
“…This positive effect of macrophyte cover on the abundance of G. carapo may be related to the biological and ecological aspects of this species. G. carapo is a multiple spawner species which exhibits territorial, parental care and building nests behavior (Campos-da-Paz, 2003;Cognato and Fialho, 2006). Besides that, it has a carnivorous feeding habit with a preference for small aquatic animals (Albert and Crampton, 2003), a lateral compressed body and a superior mouth (Campos-da-Paz, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Studies at Parque Estadual de Itapuã concerning gymnotiform species have established reproductive periods occurring from October to February for Eigenmannia trilineata (Giora & Fialho, 2009) and from November to March for Gymnotus aff. carapo (Cognato & Fialho, 2006). With this mind, the low rainfall rates and water depth observed during the months of January through April of the year studied might have induced the regression of male and female gonads and might have determined the anticipation of the end of the B. draco population breeding season.…”
Section: Discussionmentioning
confidence: 94%
“…Caudal filaments depth Level 1 = from 0 to 1.5%; Level 2 = from 1.51% to 2.5%; Level 3 = from 2.51% to 3.50%. (Silva et al, 1999;Ardanaz et al, 2001;Silva et al, 2002;Quintana et al, 2004), in photoperiod (Giora & Fialho, 2009) or in both temperature and photoperiod (Silva et al, 2003;Cognato & Fialho, 2006). For the B. draco population from lagoa Verde, the male reproductive cycle showed a positive relation with temperature, but no relation was found for photoperiod.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation